Wildlife Is a Potential Source of Human Infections of Enterocytozoon bieneusi and Giardia duodenalis in Southeastern China - Zhang, Yan; Mi, Rongsheng; Yang, Lijuan; Gong, Haiyan; Xu, Chunzhong; Feng, Yongqi; Chen, Xinsheng; Huang, Yan; Han, Xiangan; Chen, Zhaoguo (Frontiers in Microbiology, 2021)
Wildlife is known to be a source of high-impact pathogens affecting people. However, the distribution, genetic diversity and zoonotic potential of Cryptosporidium, Enterocytozoon bieneusi and Giardia duodenalis in wildlife are poorly understood. Here, we conducted the first molecular epidemiological investigation of these three pathogens in wildlife in Zhejiang and Shanghai, China. Genomic DNAs were derived from 182 individual faecal samples from wildlife, then subjected to a nested PCR-based sequencing approach for detection and characterisation. Altogether, three (1.6%), 21 (11.5%) and 48 (26.4%) specimens were test-positive for Cryptosporidium sp., E. bieneusi and G. duodenalis, respectively. Sequence analyses revealed five known (BEB6, D, MJ13, SC02 and Type IV) and two novel (designated SH_ch1 and SH_deer1) genotypes of E. bieneusi. Phylogenetically, novel E.bieneusi genotype SH_deer1 fell into Group 6 and the other genotypes were assigned to Group 1 with zoonotic potential. Three novel Cryptosporidium genotypes (Cryptosporidium avian genotype V-like and C. galli like 1 and 2) were identified, C. galli like 1&2 formed a clade that was distinct from Cryptosporidium spp.. The genetic distinctiveness of these two novel genotypes suggests that they represent a new species of Cryptosporidium. Zoonotic assemblage A (n = 36) and host-adapted assemblages C (n = 1) and E (n = 7) of G. duodenalis were characterised. The overall results suggest that wildlife act as host reservoirs carrying zoonotic E. bieneusi and G. duodenalis, potentially enabling transmission from wildlife to humans and other animals.